2013
DOI: 10.1172/jci70098
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory approaches prevent preterm birth profoundly exacerbated by gene-environment interactions

Abstract: There are currently more than 15 million preterm births each year. We propose that gene-environment interaction is a major contributor to preterm birth. To address this experimentally, we generated a mouse model with uterine deletion of Trp53, which exhibits approximately 50% incidence of spontaneous preterm birth due to premature decidual senescence with increased mTORC1 activity and COX2 signaling. Here we provide evidence that this predisposition provoked preterm birth in 100% of females exposed to a mild i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 85 publications
(94 reference statements)
3
91
0
Order By: Relevance
“…This PTB occurs in spite of high maternal serum progesterone concentrations, analogous to human pregnancy but unlike several other mouse models of PTB. Further, mice with a uterine-specific TP53 conditional knockout exhibit enhanced sensitivity to environmental triggers of PTB (89). Decidual senescence has also been identified in human PTB, suggesting that senescence pathways such as mTORC1 (mammalian target of rapamycin complex 1) may be promising targets for intervention (89).…”
Section: Emerging Disease Pathwaysmentioning
confidence: 99%
“…This PTB occurs in spite of high maternal serum progesterone concentrations, analogous to human pregnancy but unlike several other mouse models of PTB. Further, mice with a uterine-specific TP53 conditional knockout exhibit enhanced sensitivity to environmental triggers of PTB (89). Decidual senescence has also been identified in human PTB, suggesting that senescence pathways such as mTORC1 (mammalian target of rapamycin complex 1) may be promising targets for intervention (89).…”
Section: Emerging Disease Pathwaysmentioning
confidence: 99%
“…progesterone's memory effect in the uterus; the requirement for progesterone priming and its long-term effects on implantation in the mouse (Huet and Dey, 1990); blastocyst's state of activity determines the window of implantation (Paria et al, 1993); role of Cox2-derived prostaglandins and PPARδ in multiple female reproductive processes including implantation (Lim et al, 1997(Lim et al, , 1999; the role of cannabinoids/endocannabinoids in early pregnancy ; the identification of HB-EGF as the first indicator of the embryo-uterine interaction (Das et al, 1994); and findings in FKBP52 knockout mice that helped us understand progesterone sensitivity threshold requirements at different stages of pregnancy (Tranguch et al, , 2007; our unexpected finding when we moved from KUMC to Vanderbilt about diet-induced reproductive phenotype changes ; the use of cPLA2 knockout mice to understand the ripple effects throughout pregnancy, i.e., once things go wrong, full complement of pregnancy cannot be maintained (Song et al, 2002); and more recently, our findings of the importance of Msx genes and epithelial cell polarity in pregnancy (Daikoku et al, 2011) and the role of premature decidual senescence in promoting preterm birth (Hirota et al, 2010;Cha et al, 2013). These discoveries were mostly based on our studies in mouse models, but many of them have now shown clinical implications.…”
Section: What Do You Think Is Your Proudest Discovery?mentioning
confidence: 99%
“…However, most animal studies often use systemic or local exposure to high doses of inflammatory agents, such as LPS, or cytokines that induce ovarian luteolysis with a decline in blood P 4 levels and other systemic effects, resulting in PTB and/or embryonic resorptions (3). However, decline in blood P 4 levels, which triggers parturition in mice, does not appear to occur in human parturition (2,4). We generated a unique mouse model with conditional uterine deletion of tumor suppressor gene p53 (Trp53 fl/fl Pgr Cre/+ mice, referred to here as p53 d/d mice), and we showed that uterine deficiency of p53 confers premature decidual senescence and elicits spontaneous PTB without a fall in P 4 levels, thereby introducing a model to study human parturition (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…PTB in these genetically predisposed mice was greatly aggravated with exposure to even a low dose of ultrapure LPS (10 μg) with a decline in P 4 levels; this dose of LPS had no apparent adverse effects on the floxed p53 dams (p53 fl/fl dams) or their fetuses. When rapamycin and P 4 were combined and used as a treatment, the incidence of PTB in p53 d/d females given LPS was dramatically reduced (4). These results suggested that cooperative contributions from both the decidua and ovary are critical for parturition timing and pregnancy success.…”
Section: Introductionmentioning
confidence: 99%